2021
DOI: 10.1097/qad.0000000000002936
|View full text |Cite
|
Sign up to set email alerts
|

Virologic efficacy of tenofovir, lamivudine and dolutegravir as second-line antiretroviral therapy in adults failing a tenofovir-based first-line regimen

Abstract: Objective Recycling tenofovir and lamivudine/emtricitabine (XTC) with dolutegravir would provide a more tolerable, affordable, and scalable second-line regimen than dolutegravir with an optimized nucleoside reverse transcriptase inhibitor (NRTI) backbone. We evaluated efficacy of tenofovir/lamivudine/dolutegravir (TLD) in patients failing first-line tenofovir/XTC/efavirenz or nevirapine. Design Single arm, prospective, interventional study Setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 30 publications
3
40
0
Order By: Relevance
“…High levels of NRTI resistance were also reported in other studies conducted in Haiti (40.5%) [24] and Zambia (12%) [25 & ]. Although findings from recent studies [26,27,28 & ] show high levels of viral suppression among patients receiving DTG or PI despite resistance to TDF, there are limited data on the efficacy of ART when ABC effectiveness is compromised. Therefore, caution is warranted to closely monitor treatment response in young infants as well as accelerating access to paediatric formulations to newer drugs.…”
Section: Andandmentioning
confidence: 99%
See 1 more Smart Citation
“…High levels of NRTI resistance were also reported in other studies conducted in Haiti (40.5%) [24] and Zambia (12%) [25 & ]. Although findings from recent studies [26,27,28 & ] show high levels of viral suppression among patients receiving DTG or PI despite resistance to TDF, there are limited data on the efficacy of ART when ABC effectiveness is compromised. Therefore, caution is warranted to closely monitor treatment response in young infants as well as accelerating access to paediatric formulations to newer drugs.…”
Section: Andandmentioning
confidence: 99%
“…). The proportion of countries meeting the target of having at least 5% of patients on secondline ART increased from 45% (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) in 2017 to 56% (14 of 25) in 2020. Overall, most countries reported sub-optimal performance in preventing HIVDR, indicating the need to strengthen the quality and monitoring systems and implement sustainable solutions.…”
mentioning
confidence: 99%
“…The efficacy of protease inhibitors or DTG in the presence of a compromised TDF or ZDV-based NRTI backbone has been attributed to residual activity of the NRTIs, the high genetic barrier of protease inhibitors or DTG and an antagonistic effect of the M184V mutation, which causes hypersusceptibility of HIV to ZDV and TDF [5][6][7][8]. There is, however, limited direct evidence to guide recycling of ABC.…”
mentioning
confidence: 99%
“…While findings from a recent study investigating effects of recycling TDF in second-line TLD regimen and a larger randomized non-inferiority trial (i.e. NADIA trial) showed successful viral outcomes on DTG-based treatment (including in patients with prior extensive NRTI resistance), the long-term impact of pre-existing NRTI resistance on outcomes with standardised DTG-based regimens remains unclear [ 25 , 26 ]. Despite high occurrence of XTC drug resistance (as shown in Fig.…”
Section: Discussionmentioning
confidence: 99%